Wet deposition in two greek sites: Larissa and Athens - Nastos, P. T.; Papaioannou, A.; Paliatsos, A. G.; Kakavas, K.; Plageras, P.; Dovriki, E. (Fresenius Environmental Bulletin, 2008)
The determination of the chemical composition of rainfall related to the origin of the air masses, in two urban sites in Greece during the year 2006, is investigated in this study. Two model automatic rain samplers were installed, the first in the city of Larissa, Thessaly, central Greece and the second in Heraklio, Attica, a northern suburb of Athens. The concentrations (ppm) of the major cations (H+, Na+, K+, Ca2+, NH4+ and Mg2+) and major anions (NO 3-, NO2-, HCO3 -, and SO42-), as well as total hardness (ppm CaCO3), pH and electric conductivity in 25°C (μS/cm) for 27 rainfall samples -11 samples in Larissa and 16 samples in Heraklio (Athens)- were determined. In Larissa, the figures of pH range from 5.13 to 6.13 while in Heraklio (Athens), the pH within the range 5.62 to 7.88 indicates a shift of the rainfalls towards alkalinity. The electric conductivity in Larissa ranges from 16.30 μS/cm to 110.60 μS/cm and in Heraklio (Athens) from 7.00 μS/cm to 151.00 μS/cm. The analysis showed that Ca2+ and Mg2+ appear the highest concentrations out of the examined cations, while HCO 3- and SO42- present the highest concentrations within the anions. Moreover, in order to find out the origin of the air masses, the air mass back trajectories were calculated using the HYSPLIT 4 model of Air Resources Laboratory of NOAA for two different levels: 1500 and 3000 m (a.m.s.l.). © by PSP 2008.
Keywords: air mass; Air mass back trajectories; Athens; Athens [Attica]; Attica; chemical composition; concentration (composition); electrical conductivity; Eurasia; Europe; Greece; Larissa; rainfall; Southern Europe; Thessaly; urban area; Wet deposition